The Criminal Law Reform On Completion Of Samenleven In Indonesia - Sayulina, Ranie; Efendi, Roni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Pancasila as state fundamentalnorom must be reflected in the life of nation and state. Consequently, all attitudes and behavior dwell the values of Pancasila. Likewise, people as constitutive elements should also base their attitudes and behavior on Pancasila. However, there are some complex problems occurred during the development of human being. One of them is samenleven. It is a term used to describe unmarried couples who are in a relationship and live together. This samenleven behavior is certainly not corresponding with the soul of Indonesian nation. This phenomenon addresses issue that needs immediate solution. From the results of this research, it is explained that in positive law, samenleven is part of adultery. While as a part of legal reform, various efforts have been made to minimize samenleven by committing decency violations because samenleven is considered an act that destroys the sense of decency in society.